Contemporany management of the diabetic foot - Pendsey, Sharad Consultant Diabetologist; Levin, Marvin E.; Bakker, Karel (New Delhi : Jaypee, 2014)
The publication of Contemporary Management of Diabetic Foot will undoubtly eliminates misconceptions related to management of the diabetic lower limb. The list of outstanding authors being all experts in the field throughout the world will guarantee this thorough felt wish.
1. Introduction Sharad Pendsey • Goals • Methods • Project at a Glance • Impact • Results 2. Historical Notes on a Modern Disease: The Diabetic Foot Lee J Sanders • Diabetes in the Age of Antiquity • Diabetes in the Middle Ages • The Renaissance • The Seventeenth Century • The Eighteenth Century • The Nineteenth Century • The Twentieth Century • The Team Approach to Diabetes Care • Preventive Diabetic Foot Care • The Role of Neuropathy in Diabetes • Prevention of Foot Ulcers and Amputations • Understanding Causal Pathways to Amputation and Ulceration • European Initiatives in the 1990s • The Twenty-First Century • Clinical Practice Guidelines and International Consensus 3. Surgical Anatomy of the Lower Limb and Foot Shigeo Kono • Essential Anatomic Information for Foot Care • Normal Weight Bearing 4. The Global Burden of Diabetic Foot Zulfiqarali G Abbas • Introduction and Epidemiology • Characterization of the Burden of the Diabetic Foot • The Burden of the Septic Diabetic Foot • Prevention 5. Diabetic Neuropathy Andrew JM Boulton • Historical Aspects of Diabetic Neuropathy • Classification, Epidemiology and Clinical Features of the Diabetic Neuropathies • Clinical Features of Diabetic Peripheral Neuropathy • Prevention and Treatment of Diabetic Peripheral Neuropathy • Clinical Management of Diabetic Peripheral Neuropathy • Pathogenetic Treatments Contemporary Management of the Diabetic Foot • Diabetic Neuropathy and Foot Ulceration
Incluye índice
incluye ilustraciones